Examining employability skills acquisition of students in some Ethiopian universities through legitimation code theory - Sara Jehi Oumer; Meskerem Lechissa Debele; Amera Seifu Belayneh (Bahir Dar Journal of Education)
The purpose of this study was to understand the underlying principles of the acquisition of employability skills in some public Ethiopian Universities. Data were collected from 394 graduating students in the year 2021 from three Ethiopian Public Universities- Addis Ababa University, Arsi University, and Bahir Dar University. The study used Legitimation Code Theory to analyze the acquisition of employability skills. A questionnaire adapted from Maton and Howard (2016) was used to reveal legitimation codes underlying practices of employability skills acquisition. Another set of questions adopted from Nebraska University Transferable skills assessment was used to measure employability skills of students. Analysis of data was conducted using both mean and linear regression. The findings of the study revealed that all the four dimensions of specialization codes (knowledge, knower, élite, and relativist codes) are evident in the universities with regard to different sets of employability skills. The regression analysis has shown that employability skills of students can be explained by their legitimation codes.